The impact of dietary patterns on gut microbiota for the primary and secondary prevention of cardiovascular disease: a systematic review - Junwen Yu; Yue Wu; Zheng Zhu; Hongzhou Lu (Nutrition Journal)
Abstract Background Previous studies found that it is promising to achieve the protective effects of dietary patterns on cardiovascular health through the modulation of gut microbiota. However, conflicting findings have been reported on how dietary patterns impact gut microbiota in individuals either established or at risk of cardiovascular disease (CVD). Our systematic review aimed to explore the effect of dietary patterns on gut microbiota composition and on risk factors for CVD in these populations. Methods We systematically searched seven databases, including PubMed/MEDLINE, MEDLINE (Ovid), Embase (Ovid), CINHAL (EBSCO), Web of Science, CNKI (Chinese), and Wanfang (Chinese), covering literature from inception to October 2024. Studies were included if they focused on adults aged 18 years and older with CVD or at least two CVD risk factors, implemented dietary pattern interventions, and incorporated outcomes related to microbiome analysis. The risk of bias for included studies was assessed using the revised Cochrane risk of bias tool (RoB2) for randomized trials and the Risk Of Bias In Non-randomised Studies of Interventions (ROBINS-I) for non-randomized studies. Changes in the relative abundance of the gut microbiome were summarized at various taxonomic levels, including phylum, class, order, family, genus, and species. Random-effects meta-analysis was conducted to analyze the mean difference in cardiometabolic parameters pre- and post-intervention. Results Nineteen studies were identified, including 17 RCT and two self-controlled trails. Risk of bias across the studies was mixed but mainly identified as low and unclear. The most frequently reported increased taxa were Faecalibacterium (N = 8) with plant-rich diets, Bacteroides (N = 3) with restrictive diets, and Ruminococcaceae UCG 005 and Alistipes (N = 9) with the polyphenol-rich diets. The most frequently reported decreased taxa were Parabacteroides (N = 7) with plant-rich diets, Roseburia (N = 3) with restrictive diets, and Ruminococcus gauvreauii group (N = 6) with the polyphenol-rich diets. Plant-rich diets showed a significant decrease in total cholesterol (TC) with a mean difference of -6.77 (95% CI, -12.36 to -2.58; I 2  = 84.7%), while restrictive diets showed a significant decrease in triglycerides (TG) of -22.12 (95% CI, -36.05 to -8.19; I 2  = 98.4%). Conclusions Different dietary patterns showed distinct impacts on gut microbiota composition. Plant-rich diets promoted the proliferation of butyrate-producing bacteria, suggesting promising prospects for modulating gut microbiota and butyrate production through dietary interventions to enhance cardiovascular health. Further research is warranted to investigate the long-term effects of dietary patterns on clinical endpoints, such as CVD events or mortality. Review registration Registration number: CRD42024507660